2008
DOI: 10.1007/s11116-008-9180-x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying optimal data aggregation interval sizes for link and corridor travel time estimation and forecasting

Abstract: Travel time estimation, Travel time forecasting, Aggregation Interval, Traffic information,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Further, the form of the dependent variables in the statistical models, whether aggregated or disaggregated as well as the aggregation interval is proven to impact the study results [ 9 ]. In fact, the optimum aggregation interval for loop detector data (i.e., speed data) depends on the purpose of the application and traffic conditions [ 22 ]. Moreover, many researchers queried about the functional form to be used in modelling the impacts of road-weather conditions on traffic stream characteristics of uninterrupted flow [ 9 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, the form of the dependent variables in the statistical models, whether aggregated or disaggregated as well as the aggregation interval is proven to impact the study results [ 9 ]. In fact, the optimum aggregation interval for loop detector data (i.e., speed data) depends on the purpose of the application and traffic conditions [ 22 ]. Moreover, many researchers queried about the functional form to be used in modelling the impacts of road-weather conditions on traffic stream characteristics of uninterrupted flow [ 9 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although studies in the existing literature predominantly use data aggregated over 5 min and 15 min intervals, some prior studies have investigated the effect of data resolution on the reliability of the predictions provided by the corresponding models; the results have, however, been inconclusive. For instance, Park et al [7] investigated the effect of aggregation on travel time prediction and considered aggregation levels from 2 min to 60 min in the context of an ARIMA model. ey concluded that higher levels of aggregation were required to forecast route travel time than when forecasting link travel times.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is necessary to consider the optimal data aggregation interval size for various lev-els (link, corridor, etc.) of estimation given the individual samples of probes (39).…”
Section: Improved Travel Timementioning
confidence: 99%